Expansion of IL-23 receptor bearing TNFR2+ T cells is associated with molecular resistance to anti-TNF therapy in Crohn's disease. Issue 5 (30th May 2018) - Schmitt, Heike; Billmeier, Ulrike; Dieterich, Walburga; Rath, Timo; Sonnewald, Sophia; Reid, Stephen; Hirschmann, Simon; Hildner, Kai; Waldner, Maximilian J; Mudter, Jonas; Hartmann, Arndt; Grützmann, Robert; et al.
Abstract : Objective: Anti-tumour necrosis factor (TNF) antibodies are successfully used for treatment of Crohn's disease. Nevertheless, approximately 40% of patients display failure to anti-TNF therapy. Here, we characterised molecular mechanisms that are associated with endoscopic resistance to anti-TNF therapy. Design: Mucosal and blood cells were isolated from patients with Crohn's disease prior and during anti-TNF therapy. Cytokine profiles, cell surface markers, signalling proteins and cell apoptosis were assessed by microarray, immunohistochemistry, qPCR, ELISA, whole organ cultures and FACS. Results: Responders to anti-TNF therapy displayed a significantly higher expression of TNF receptor 2 (TNFR2) but not IL23R on T cells than non-responders prior to anti-TNF therapy. During anti-TNF therapy, there was a significant upregulation of mucosal IL-23p19, IL23R and IL-17A in anti-TNF non-responders but not in responders. Apoptosis-resistant TNFR2+IL23R+ T cells were significantly expanded in anti-TNF non-responders compared with responders, expressed the gut tropic integrins α4β7, and exhibited increased expression of IFN-γ, T-bet, IL-17A and RORγt compared with TNFR2+IL23R− cells, indicating a mixed Th1/Th17-like phenotype. Intestinal TNFR2+IL23R+ T cells were activated by IL-23 derived from CD14+ macrophages, which were significantly more present in non-responders prior to anti-TNF treatment. Administration of IL-23 to anti-TNF-treated mucosal organ cultures led to the expansion of CD4+IL23R+TNFR2+ lymphocytes. Functional studies demonstrated that anti-TNF-induced apoptosis in mucosal T cells is abrogated by IL-23. Conclusions: Expansion of apoptosis-resistant intestinal TNFR2+IL23R+ T cells is associated with resistance to anti-TNF therapy in Crohn's disease. These findings identify IL-23 as a suitable molecular target in patients with Crohn's disease refractory to anti-TNF therapy.